Stabilizing Intergovernmental Transfers in Latin America : A Complement to National/Subnational Fiscal Rules? - Gonzalez, Christian Y. (World Bank, Washington, DC, 2014)
The traditional theory of fiscal federalism assigns the role of macroeconomic stabilization to the federal government. In addition to this long-standing theoretical result, there is empirical observation that federal governments in developing countries typically have cheaper and more stable access to capital markets, relative to subnational governments. Drawing on the recent experience of four large federal countries in Latin America-Argentina, Brazil, Colombia, and Mexico--the authors examine how intergovernmental transfers affect the division of the burden of stabilization across the levels of government, when the nation as a whole faces economic fluctuations. Imposing stabilizing rules on federal transfers that protect subnational governments from fluctuations in the business cycle can serve two purposes. During boom periods, stabilizing rules prevent subnational governments' tendency to increase inflexible expenditures. And during downturns, stabilizing rules place the burden of borrowing at the federal level-the level most appropriate for macroeconomic stabilization and often the level with superior access to credit. Despite the logic of these rules, recent experience of the four countries reveals that these rules can be risky, particularly in the face of high GDP volatility. Protection against falling revenues in the downturn constitutes a contingent liability for the central government. Argentina's stabilizing rule contributed to fiscal and political tensions during its ongoing crisis. Colombia is beginning to implement similar rules. Meanwhile, Brazilian and Mexican transfers do not implement such rules and fiscal and economic results do not appear to have fared any worse for this absence. The authors draw on the country experience to establish that certain conditions should be in place before establishing a stabilization rule to federal-to-subnational fiscal transfers-in particular the elimination of long-term structural fiscal imbalances, either within levels of government or across levels of government.